Mekanisme Tensegritas Sel dan Regulasi Imun oleh mikroRNA : Memahami Interaksi Kompleks dalam Sistem Imun Mamalia - Teuku Daffa Hasian; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Modern cellular tissues have evolved into cell tensegrity structures, where cell strength and stability are established through supportive interactions. Tensegrity improves the efficiency of frequency spectrum use and signal quality in cellular networks. Research shows miRNAs play an important role in the regulation of gene expression in the immune system, providing new insights into the complexity of modern biological systems. Structural Design of Cellular Tissues involves computer simulation studies and laboratory experiments on cell tensegrity. Immune Regulation by MicroRNAs includes analysis of MiRNA gene expression and functionality using technologies such as microarrays and high-throughput sequencing. Data Integration includes identifying microRNA gene targets and understanding transcriptional regulation through methods such as reporter gene assays and Chromatin Immunoprecipitation to predict cellular responses in clinical scenarios. The complex interplay between cellular tensegratas mechanisms and immune regulation by microRNAs shows how widespread their interactions are in human biological systems. The cellular tensegratas structure helps improve intercellular communication, while immune regulation by microRNAs ensures the body's proper response to pathogens. Recent research on microRNAs has exposed their role in the development and function of mammalian immune cells. MiRNAs play an important role in the development and function of mammalian immune cells. The complex interactions between cellular tensile mechanisms and immune regulation by microRNAs demonstrate how structural and functional integration can improve the performance of human biological systems. Integration of these data provides a complete picture of the complexity of modern biological systems and their clinical implications in the diagnosis and treatment of immunological diseases.